Adhesive bond thickness inversion using through transmission data - Volker, A.W.F.; Jansen, H.P. (BINDT, 2025)
Bonded metal panels are frequently used in aircraft structures. Non-destructive inspections are performed to ensure the integrity of these panels. A commonly applied method is through transmission ultrasonic inspection. Due to the layered structure of these panels, the transmission response is strongly frequency dependent and consists of a series of resonance peaks. Even a small thickness variation in the bondline causes a strong imprint in C-scan images. This imprint is generally considered as an undesired output, complicating the interpretation of the inspection. Bondline thickness variations may affect the mechanical properties of the panel. As the imprint contains information about the actual thickness of each individual bondline, this data could be utilized to assess the mechanical properties of the bonded structure. This resonance pattern can be calculated using a simple 1D-transmission model. An inversion scheme has been developed to determine the local bondline thickness of each individual bondline from transmission data. The uniqueness of the solution is studied for panels with three bondlines. The approach has been evaluated on aluminium bonded panels with one and three bondlines. Using the estimated bondline thicknesses and the thickness of the individual aluminium panels the total panel thickness can be calculated, which shows good agreement with reference measurements.